ANALISIS PROGRAM PELATIHAN GURU DALAM MENERAPKAN KURIKULUM BERBASIS CINTA DI MADRASAH IBTIDAIYAH - Amilatul Afifah; Ariya Ayu Purbasari; Fatma Zahro’ul Afifah; Ines Paradina; Rachmania; Suttrisno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of teacher training programs in implementing the Love-Based Curriculum (KBC) in Islamic Elementary Schools (Madrasah Ibtidaiyah) as an effort to strengthen teachers' pedagogical, affective, and implementative competencies in humanistic and compassionate learning. The Love-Based Curriculum is an Islamic educational innovation that places compassion, empathy, and care as the main foundation of the learning process to shape the holistic and reflective character of students. This study uses a qualitative descriptive approach through a literature review and synthesis of empirical findings from recent studies on teacher training related to the KBC. The results of the study indicate that structured and sustainable training programs play a significant role in improving teachers' understanding of the principles of the KBC, relevant learning strategies, and their ability to internalize the value of compassion in classroom practice. However, the main challenges remain the limitations of intensive training, adequate learning resources, and support for implementation policies at the school level. The implications of these findings indicate that strengthening teacher capacity through various training programs is a key element in the successful implementation of the KBC in Islamic Elementary Schools, as well as being an important foundation for the development of more humanistic and meaningful student character.